EFEKTIVITAS LAYANAN BIMBINGAN KLASIKAL UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS X E 5 DI MAN 2 BUKITTINGGI - Yeni Febrianti; Syawaluddin; Intan Permata Sari (CV. ADIBA AISHA AMIRA, 2024)
This research aims to determine the effectiveness of classical guidance services to increase students' self-confidence at MAN 2 Bukittinggi. The subjects in this research were students from MAN 2 Bukittinggi who had low levels of self- confidence. The approach used in this research is a quantitative approach. The quantitative approach is systematic scientific research into parts and phenomena and their relationships. The type of research used in this research is experimentation. The research design used in this research is a pre-experimental design with a one-group pre-test pro-test model. The data collection method uses a questionnaire. The questionnaire contains statements regarding student self- confidence. The results of the research are, the results of the Wilcoxon test calculation which obtained a significant result of 0.000. Based on applicable regulations, it is known that the Wilcoxon sig test. P-value 0.000 < 0.05 according to these results it can be said that the use of classical guidance services to increase students' self-confidence was successful. It can be concluded that classical guidance services can increase students' self-confidence at MAN 2 Bukittinggi